The 2009 A(H1N1) Influenza Pandemic in the French Armed Forces: Epidemiological Surveillance and Operational Management. Issue 2 (1st February 2014) - Pohl, Jean-Baptiste; Mayet, Aurélie; Bédubourg, Gabriel; Duron, Sandrine; Michel, Rémy; Deparis, Xavier; Rapp, Christophe; Godart, Patrick; Migliani, René; Meynard, Jean-Baptiste
ABSTRACT: Objective: The main objective of this study was to evaluate the contribution of a newly implemented daily surveillance system to the management of the 2009 A(H1N1) influenza pandemic by the military decision-makers at different levels in the French Department of Defence. Methods: The study sample included all medical advisors in the Ministry of Defence and the French Armed Forces Staff and also the members of the specific committee dedicated to flu pandemic control. The variables studied were mental representation of epidemiology, relevance, usefulness, and real-time use of surveillance data using quantitative questionnaires and qualitative face-to-face semistructured interviews. Results: Among the risk managers of the flu pandemic in the Armed Forces, 84% responded. The data generated by epidemiological surveillance were considered relevant and useful, and were reported as effectively used. On the basis of the information produced, concrete actions were planned and implemented in the French Armed Forces. Conclusion: In a pandemic situation involving low mortality, the daily monitoring of the disease did not target public health issues, but it was mainly used to assess the availability of the Armed Forces in real time. For the military staff, epidemiological surveillance represents an essential information tool for the conduct of operations.